TM

\(\dfrac{2\left(9+2x\right)}{x^2-9}=\dfrac{2}{x-3}-\dfrac{1}{x+3}help\)

TL
11 tháng 6 2021 lúc 9:36

ĐK: `x \ne \pm 3`

`(2(9+2x))/(x^2-9)=2/(x-3)-1/(x+3)`

`<=>2(2x+9)=2(x+3)-(x-3)`

`<=>4x+18=2x+6-x+3`

`<=>4x+18=x+9`

`<=>3x=-9`

`x=-3 (L)`

Vậy `S=∅`.

Bình luận (0)
KH
11 tháng 6 2021 lúc 9:39

\(\dfrac{2\left(9+2x\right)}{x^2-9}=\dfrac{2}{x-3}-\dfrac{1}{x+3}\)

\(\Leftrightarrow\dfrac{18+4x}{\left(x-3\right)\left(x+3\right)}-\dfrac{2\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}+\dfrac{x-3}{\left(x-3\right)\left(x+3\right)}=0\)

\(\Rightarrow18+4x-2x-6+x-3=0\)

\(\Leftrightarrow3x+9=0\)

\(\Leftrightarrow3\left(x+3\right)=0\)

\(\Leftrightarrow x+3=0\)

\(\Leftrightarrow x=-3\)

\(S=\left\{-3\right\}\)

 

Bình luận (0)
PG
11 tháng 6 2021 lúc 9:39

ĐKXĐ:       x ≠ 3  ; x ≠  -3

    \(\dfrac{2\left(9+2x\right)}{x^2-9}=\dfrac{2\left(x+3\right)}{x^2-9}-\dfrac{x-3}{x^2-9}\)

⇒  \(2\left(9+2x\right)=2\left(x+3\right)-1\left(x-3\right)\)

Ta có: \(2\left(9+2x\right)=2\left(x+3\right)-1\left(x-3\right)\)

              \(18+4x=2x+6-x+3\)

       \(4x-2x+x=6+3-18\)

                       \(3x=0\)

                 \(\Rightarrow x\) vô nghiệm

Vậy phương trình vô nghiệm

Bình luận (0)